Distribution of Inclusions in 18CrNiMo7-6 Steel Billet and Its Relationship with Inclusion Compositions. (November 2020) - Wang, N.; Fang, C.F.; Zhao, L.; Huang, K.; Wang, R.; Wang, J.M.; Hao, H.
Abstract: The 18CrNiMo7-6 steel billet was prepared by the process of EBT→LF→VD→die casting and forging. The position distribution, composition, type and cause of inclusions in the billet were statistically analysed by ASPEX and scanning electron microscopy. The results show that there are obvious distribution differences of inclusions in different parts of the steel billet. In contrast, the number density of inclusions in the billet corresponding to the ingot riser and the negative segregation zone is higher; the average composition point of the inclusions in the slow cooling zone tends to be distributed in the higher temperature zone of the MgO-Al2 O3 -CaO ternary phase diagram.